A60 THE INCIDENCE OF INFLAMMATORY BOWEL DISEASE IS DECREASING IN SASKATCHEWAN: A POPULATION-BASED COHORT STUDY. (26th February 2020) - Osei, J A; Peña-Sánchez, J; Fowler, S; Muhajarine, N; Kaplan, G G; Lix, L M
Abstract: Background: Canada has one of the highest inflammatory bowel disease (IBD) incidence rates worldwide, although within Canada rates vary. Evidence show increasing incidence rates of IBD in Ontario (i.e. adults aged 30–60), stable in Alberta and decreasing in Manitoba. Additionally, higher incident rates of IBD have been identified among urban regions compared to rural regions. There is limited data on the incidence of IBD in Saskatchewan. Aims: The study objectives were to 1) estimate IBD incidence rates in Saskatchewan from 1999 to 2016, and 2) test for differences in IBD incidence rates for rural and urban regions of Saskatchewan. Methods: A population-based study was conducted using linked provincial administrative health databases. Individuals age 18+ old with newly diagnosed Crohn's disease (CD) or ulcerative colitis (UC) were identified using a validated case definition. Generalized linear models with a negative binomial distribution were used to estimate incidence rates and incidence rate ratios (IRR) adjusted for age group, sex, and rurality with 95% confidence intervals (95%CI). Results: In total, 4, 908 newly diagnosed individuals with IBD were included. The average annual incidence rate of IBD decreased from 75 (95%CI 67–84) per 100, 000 people in 1999 to 15 (95%CI 12–18) per 100, 000 population in 2016. This decrease was evident in both UC (from 36/100, 000 [95%CI 31–42] in 1999 to 6/100, 000 [95%CI 4–8] in 2016) and CD (37/100, 000 [95%CI 32–42] in 1999 to 8/100, 000 [95%CI 6–10] in 2016). A significant decline of 6.9% (95%CI 6.2–7.6) in the average annual incidence of IBD was estimated between 1999 and 2016 (see Figure 1). Urban residents had a greater overall risk of IBD (IRR=1.19, 95%CI 1.11–1.27) than rural residents. This risk difference was statistically significant for CD (IRR=1.25, 95%CI 1.14–1.36), but not UC (IRR=1.08, 95%CI 0.97–1.19). Conclusions: A decreasing trend in IBD incidence in Saskatchewan was identified after adjusting for age group, sex, and rural/urban region of residence. Around 150 new cases of IBD are still diagnosed annually in Saskatchewan, but this estimate is lower than estimates from other provinces. Urban dwellers have a 25% higher risk of CD onset compared to their rural counterparts. This finding could suggest the presence of specific risk factors in urban settings that require further investigation. Health care providers and decision-makers should plan IBD-specific health care programs taking into account these specific IBD rates in Saskatchewan. Funding Agencies: College of Medicine, University of Saskatchewan